Evaluation of The Deleterious Effects of Aqueous Fruit Extract of Abelmoschus Esculentus (Okro Fruit) on Some Male Reproductive Parameters in Sprague Dawley Rats - F.O. Awobajo, I.I. Olatunji-Bello, T. Ijiwole, (Journal of Phytology, 2009)
Objective: The reversible reproductive impact of oral administration of methanol fruit extract of Abelmoschus esculentus was assessed in pubertal male Sprague Dawley rats. Design: The animals were divided into the following groups; Control group (six rats), Extract-treated (seven rats), One week of recovery group (five rats), two weeks recovery group (five rats). A dose of 70mg/kg body weight/day of methanol fruit extract ofÃ‚Â  A. esculentus was given orally to the extract treated, one-week recovery and two-weeks recovery groups respectively for a period of four weeks (28days). The recovery groups were left untreated after the four weeks for one and two weeks respectively. Results: Methanol fruit extract of A. esculentus significantly reduced (P<0.05) gross sperm motility, sperm count, life/dead ratio and it increased the occurrence of abnormal sperm cell in the semen sample. Methanol fruit extract of A. esculentus had no effect on epidydimal volume neither did it have any significant effect on both testosterone and luteinizing hormone serum levels (P>0.05). Methanol fruit extract of A. esculentus reduced the mean weight of testes; this is supported by the histological studies which showed testicular atrophy. There was significant reduction in the weight of the prostate gland. On the other hand, methanol fruit extract of A. esculentus significantly increased body weight (P<0.05). These effects were reversed after two weeks recovery period. Conclusion: These results showed that oral administration of methanol fruit extract of A. esculentus produced a reversible reduction in male fertility assessment parameters in male rats.